Preparation, characterization, and protective effects of Gardenia fructus carbon dots against oxidative damage induced by LPS in IPEC-J2 cells - Chen, Bai-lu; Zang, Xin-yi; Mo, Jia-rong; Zhang, Ruo-yi; Wang, Heng; Wang, Quan-xi; Li, Jian (Frontiers in Cellular and Infection Microbiology, 2024)
This study aimed to prepare Gardenia fructus carbon dots (GF-CDs) and examine their efficacy in mitigating oxidative stress and apoptosis in intestinal porcine epithelial cells from the jejunum (IPEC-J2 cells) induced by lipopolysaccharide (LPS). The GF-CDs were synthesized using a one-step hydrothermal method. The oxidative damage model of IPEC-J2 cells was induced through LPS treatment. The potential mechanism by which GF-CDs affect cellular oxidative damage was examined through the perspectives of apoptosis, reactive oxygen species level, antioxidant-related enzyme index, mRNA transcription of antioxidant-related genes, and the expression of antioxidant proteins. The results revealed that GF-CDs, characterized by particle sizes<7 nm, abundant functional groups, and good water solubility, were synthesized using a one-step hydrothermal method. The carbon spots of Gardenia fructus at concentrations of 50, 100, and 200 μg/mL exhibited protective effects, as evidenced by their ability to enhance viability (P<0.01) and restore cellular morphology after oxidative damage. The GF-CDs decreased oxidative damage and reduced the apoptosis rate of cells by upregulating AKT1 expression and downregulating the expression of Caspase 3, STAT3, TNF-α, and JNK. These results indicate that GF-CDs have the characteristic physicochemical properties of CDs, exhibit biological activities related to antioxidation and cellular damage mitigation, and may serve as a potential healthcare product in swine raising.